Rectal NETs and rectosigmoid junction NETs may need to be treated differently. (16th December 2019) - Cai, Wen; Ge, Weiting; Hu, Hanguang; Mao, Jianshan
Abstract: Neuroendocrine tumors (NETs) are heterogeneous, and the incidence of NETs is rapidly increasing. We observed different survival in patients with rectal NETs and rectosigmoid junction NETs, which are treated similarly. We included patients with rectal and rectosigmoid junction NETs from the SEER database. The 5‐year survival was set as the end‐point. 6675 patients with rectal NETs and 329 patients with rectosigmoid junction NETs, were eligible for the analysis. Initially, the survival analyses suggested that the 5‐year survival significantly differed between the patients with rectal and rectosigmoid junction NETs (HR = 0.82, 95% CI 0.70‐0.95; P  = .01). Tumor differentiation, an invasion deeper than T2, and lymph node and distant metastases were still important risk factors affecting survival for both location. While, the males showed better survival (HR = 0.69, 95% CI 0.55‐0.88; P  < .01) and primary tumor surgery had no benefits ( P  = .56) for patients with rectosigmoid junction NETs. The factors that predict regional lymph node metastases varied by location. In rectal NETs, invasion deeper than T1 and a tumor larger than 1 cm could significantly increase the risk of regional lymph node metastases (all OR > 5, P  < .01). In rectosigmoid junction NETs, the risk of regional lymph node metastases was considered significantly higher with invasion deeper than T1 (all OR > 5, P  < .01) and a tumor larger than 2 cm (OR = 31.32, 95% CI 2.53‐387.57; P  < .01). We advocate a clear and consistent definition of the rectosigmoid junction for future studies, and more studies are needed to determine the reason underlying differences between rectum and rectosigmoid junction. Abstract : Survival and risk factors of rectal and rectosigmoid junction NET are different. Rectosigmoid junction NETs presented a better 5‐year survival. A clear and consistent definition of the rectosigmoid junction is urgently needed for future studies.